The Importance of Investments for Young People - Popovych, S. V. (My University, 2020)
Young people today face many diverse aspects of adult lives. One of these is investment. Investment is a kind of act where assets are purchased which helps an individual to earn profit in the future. In other words, it means investing your money to make more money. The purpose of investment is financial security in the long run. The more early you invest the more profit you can avail out of your money. But is this common among young people? Do they consider it necessary?
Keywords: investment; money; financial security